Pidie Regency Government Agencies, the Application of Government Accounting to the Acquisition of "Unqualified (WTP)" Status has been Approved for the 2015-2020 Period (According to Government Regulation of the Minister of Home Affairs No. 13 Year 2006) - Italina, Cut; Herizal, Herizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study was to ascertain the Pidie District Government's strategy for retaining WTP opinions on accrual-based financial statements. The descriptive qualitative approach was used in this study, along with a case study method and data collection via interviews. The study's findings indicated that the financial statements used to maintain the WTP opinion were prepared using a variety of methods, including increased commitment between leaders and their subordinates, improved management of regional property and receivables, increased the quality of human resources, team formation, improved information technology, and increased the inspectorate's role as an auditor. Obstacles to retaining the WTP's viewpoint include inefficient SIAP applications and job transfers.